Development of the COVID-19 Stigma Perception Scale - Gülay İpekçoban; Reva Balcı Akpınar; Elif Kant (Atatürk University, 2024)
Objective: The aim of this study is to develop a valid and reliable measurement tool to be used to determine the stigma perception experienced by individuals with COVID-19 during the disease process. Methods: The study was conducted in the methodological research type. The data of the study were collected with the draft COVID-19 Stigma Perception Scale developed by the researchers between March and June 2021. The study included 316 individuals who had COVID-19 disease.Results: Explanatory and Confirmatory factor analysis was used to evaluate the scale's factor structure, yielding a 3-dimensional structure that explained 47.76 per cent of the overall variation. The compatibility values of the scale were found as X2/Sd =2.17, RMSEA= .060, SRMR=.05, NFI =.80, CFI = .90, GFI =.85, AGFI= .80 and TLI = .90. Internal consistency, two-half reliability analyses, and item analyses were conducted to be able to determine the reliability of the scale, as a result of which adequacy was attained for the reliability of the scale.Conclusion: As a result of this research, it has been determined that and 37-item scale developed to evaluate the perception of COVID-19 stigma is both a valid and reliable measurement tool. This scale should be tested and used for different languages and cultures.